Study of b-hadron decays to Λ+c h−h′− final states - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2024)
Decays of Ξ −b and Ω−b baryons to Λ+c h−h′− final states, with h−h′− being π−π−, K−π− and K−K− meson pairs, are searched for using data collected with the LHCb detector. The data sample studied corresponds to an integrated luminosity of 8.7 fb−1 of pp collisions collected at centre-of-mass energies √s = 7, 8 and 13 TeV. The products of the relative branching fractions and fragmentation fractions for each signal mode, relative to the B− → Λ+c pπ− mode, are measured, with Ξ −b → Λ+c K−π−, Ξ −b → Λ+c K−K− and Ω−b → Λ+c K−K− decays being observed at over 5 σ significance. The Ξ −b → Λ+c K−π− mode is also used to measure the Ξ −b production asymmetry, which is found to be consistent with zero. In addition, the B− → Λ+c pK− decay is observed for the first time, and its branching fraction is measured relative to that of the B− → Λ+c pπ− mode.
Im Titel sind die Zeichen "+" und "-" hochgestellt
The LHCb collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C.E. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, F. Glaser, P.A. Günther, X. Han, S. Hausmann-Menzemer, P. Herrero Gascon, J. Hu, J. Kubat, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, P.R. Pais, S.R. Roy, M. Ruiz Diaz, M. Schmelling, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, M. Zavertyaev, Y. Zhao, A. Zhelezov und weitere 1063
Gesehen am 09.10.2025